Diabetes increases mortality in patients with pancreatic and colorectal cancer by promoting cachexia and its associated inflammatory status - Alexandra Chovsepian; Olga Prokopchuk; Gabriela Petrova; Tefta Gjini; Hanna Kuzi; Simone Heisz; Klaus-Peter Janssen; Marc E. Martignoni; Helmut Friess; Hans Hauner; Maria Rohm (Molecular Metabolism, 2023)
Objectives: Cancer is considered an emerging diabetes complication, with higher incidence and worse prognosis in patients with diabetes. Cancer is frequently associated with cachexia, a systemic metabolic disease causing wasting. It is currently unclear how diabetes affects the development and progression of cachexia. Methods: We investigated the interplay between diabetes and cancer cachexia retrospectively in a cohort of 345 patients with colorectal and pancreatic cancer. We recorded body weight, fat mass, muscle mass, clinical serum values, and survival of these patients. Patients were grouped either into diabetic/non-diabetic groups based on previous diagnosis, or into obese/non-obese groups based on body mass index (BMI ≥30 kg/m2 was considered obese). Results: The pre-existence of type 2 diabetes, but not obesity, in patients with cancer led to increased cachexia incidence (80%, compared to 61% without diabetes, p ≤ 0.05), higher weight loss (8.9% vs. 6.0%, p ≤ 0.001), and reduced survival probability (median survival days: 689 vs. 538, Chi square = 4.96, p ≤ 0.05) irrespective of the initial body weight or tumor progression. Patients with diabetes and cancer showed higher serum levels of C-reactive protein (0.919 μg/mL vs. 0.551 μg/mL, p ≤ 0.01) and interleukin 6 (5.98 pg/mL vs. 3.75 pg/mL, p ≤ 0.05) as well as lower serum albumin levels (3.98 g/dL vs. 4.18 g/dL, p ≤ 0.05) than patients with cancer without diabetes. In a sub-analysis of patients with pancreatic cancer, pre-existing diabetes worsened weight loss (9.95% vs. 6.93%, p ≤ 0.01), and increased the duration of hospitalization (24.41 days vs. 15.85 days, p ≤ 0.001). Further, diabetes aggravated clinical manifestations of cachexia, as changes in the aforementioned biomarkers were more pronounced in patients with diabetes and cachexia co-existence, compared to cachectic patients without diabetes (C-reactive protein: 2.300 μg/mL vs. 0.571 μg/mL, p ≤ 0.0001; hemoglobin: 11.24 g/dL vs. 12.52 g/dL, p ≤ 0.05). Conclusions: We show for the first time that pre-existing diabetes aggravates cachexia development in patients with colorectal and pancreatic cancer. This is important when considering cachexia biomarkers and weight management in patients with co-existing diabetes and cancer.